Correlation of Complex Impacted Mandibular Teeth with Pericoronitis and Effect of Minimally Invasive Tooth Extraction on Patients' Long-term Outcome of Masticatory Ability. (17th October 2022) - Nie, Tinghong; Chang, Bojie; Tian, Lili; Cao, Shansong; Wang, Junjie; Qi, Haitao; Gao, Lirong
Abstract : Objective . To explore the correlation of complex impacted mandibular teeth and pericoronitis, as well as the effect of minimally invasive tooth extraction on patients' long-term outcomes of masticatory ability. Methods . A total of 101 patients with complex impacted teeth who were treated in our hospital from March 2019 to June 2021 were selected and divided into the control group ( n  = 55) and the observation group ( n  = 46) according to the different treatment methods. The patients in the control group were given conventional extraction treatment, and the patients in the observation group were given minimally invasive extraction treatment. The clinicopathological features of patients complicated by pericoronitis were observed and the relationship between complex impacted mandibular teeth and pericoronitis was discussed. Additionally, we made statistics on operative time (OT), intraoperative blood loss (IBL), dental socket integrity score, and adverse reactions (ARs) and compared the clinical efficacy between the observation group and control group. The Visual Analogue Scale (VAS) and Oral Health Impact Profile scale (OHIP-14) were utilized for pain assessment and oral health status evaluation, respectively. Bite force (BF) and masticatory efficiency were also measured. Results . OG showed less OT and IBL than CG, with a higher dental socket integrity score (P < 0.05 ). In addition, OG outperformed CG with a higher overall response rate and a lower incidence of ARs (P < 0.05 ). The pretreatment VAS score, mouth-opening degree, and OHIP-14 score differed insignificantly between groups (P > 0.05 ). After treatment, the VAS score of OG decreased, while the mouth-opening degree and OHIP-14 score increased (P < 0.05 ). Finally, the mastication ability was higher in OG at 7 days postoperatively, but there was no difference between groups at 6 months postoperatively (P > 0.05 ). Conclusion . Complex mandibular impacted teeth can easily induce pericoronitis, so clinicians should pay attention to the influencing factors of pericoronitis. Minimally invasive surgery for complex impacted mandibular teeth can effectively improve treatment outcomes, accelerate patient rehabilitation, and provide more effective protection for patients' oral health and masticatory ability, which is worth promoting in clinical use.